A latent profile analysis of category characteristics of learning engagement, achievement motivation and its influencing factors among Chinese medical students - Wu, Xiaoguang; Shi, Wenxiang; Song, Xuemeng; Di, Siyu (Frontiers in Psychology, 2025)
PurposeThis study aimed to investigate the heterogeneity of learning engagement and achievement motivation among medical students, understand the role of career calling in predicting the subcategories of learning engagement and achievement motivation among medical students, and provide empirical evidence for medical education reform.MethodsLatent profile analysis was used to investigate the latent characteristic patterns of learning engagement and achievement motivation, while polynomial logistic regression was used to investigate the predictive role of a sense of career using the latent categories of learning engagement and achievement motivation. The Learning Engagement Scale, Achievement Motivation Scale, and Career Calling Scale were used to survey students in their freshman and junior years (n = 1930) at a medical undergraduate college in Anhui Province, China.Results(1) Positive associations were found between achievement motivation, learning engagement, and sense of career calling among medical students. (2) Five latent profiles of medical students’ learning engagement and achievement motivation were identified: “avoidant learners,” “negative learners,” “positive learners,” “enjoyable learners,” and “excessive learners.” The vast majority of medical students were classified as “avoidant learners” or “negative learners.” This suggests that the current level of learning engagement among medical students is low. (3) Medical students’ perceptions of their career calling have a considerable impact on the latent categories of learning engagement and achievement motivation. Specifically, “positive learners” have the strongest sense of career calling, followed by “excessive learners,” “enjoyable learners,” and “avoidant learners,” and the lowest by “negative learners.”ConclusionHeterogeneity appears in medical students’ learning engagement and achievement motivation, with clear categorical traits and a strong correlation with career calling. The level of medical students’ learning engagement can be improved by stimulating their achievement motivation and increasing their career calling.